Bio/hydrochar Sorbents for Environmental Remediation. Issue 4 (9th April 2020) - Zhang, Xingguang; Wang, Yang; Cai, Junmeng; Wilson, Karen; Lee, Adam F.
Abstract : A rising global population and aspirational higher living standards has driven a step change in resource utilization and concomitant anthropogenic pollution across the biosphere. Low‐cost and scalable technologies for environmental remediation are therefore urgently sought, with an emphasis on trash‐to‐treasure strategies that exploit abundant but underutilized waste by‐products of existing sectors. Biochars are carbon‐rich, porous solids produced by biomass pyrolysis under anaerobic or oxygen‐scarce conditions at high temperature (350–700 °C), while hydrochars are produced by hydrothermal biomass carbonization at lower temperature (130–250 °C) and high autogenous pressures (0.3–4.0 MPa). Bio/hydrochars possess unique physicochemical properties, notably high surface areas (100–1500 m 2  g −1 ) and porosity (0.25–2.5 cm 3  g −1 ) and rich surface chemistry featuring carboxylic, phenolic, hydroxyl, and carbonyl functions, amenable to chemical, physical, or biochemical modification, rendering them ideal sorbents for pollutants such as heavy metals (e.g. As and Cr), and toxic organic (e.g., dyes and xenobiotics) and inorganic (e.g., SO2 ) molecules. Bio/hydrochars are attractive for environmental remediation of pollutant mixtures by surface complexation, redox chemistry, electrostatic interactions/ion exchange, or co‐precipitation. This review discusses recent opportunities and challenges in creating bio/hydrochar sorbents and their nanocomposites through grafting, doping, and chemical/physical activation, for the depollution of aquatic and atmospheric environments. Abstract : Biomass valorisation offers sustainable chemical/energy production and the creation of high value functional materials for environmental remediation.